CHALLENGES AND SOLUTIONS IN IMPLEMENTING CLIL: TEACHERS’ PERSPECTIVES FROM PRIMARY EDUCATION - Rifaldi Setia Negara; Hastowohadi; Mia Leonor Rafol (Pena Cendekia Insani, 2025)
This study uses a qualitative approach with the aim of understanding the phenomenon of challenges and solutions in the implementation of CLIL (Content and Language Integrated Learning) in Elementary education in depth through the perspective of participants. Data were collected through in-depth interviews, classroom observations, and documentation involving CLIL classes At Suantou Elementary School, Chiayi County, Taiwan. Data analysis was conducted thematically with the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that teachers face obstacles in the aspect of linguistic competence, while from a pedagogical perspective they are able to present innovative strategies such as code-switching, the use of digital media, project-based learning, and collaboration between teachers. Student responses showed high motivation when contextual, interactive, and bilingual learning, although there were still obstacles when English was fully used. This study contributes to theoretical, practical, and policy implications, particularly regarding improving CLIL teacher competence, supporting student motivation, and innovation in learning strategies. In addition, this study provides new insights into CLIL implementation in Elementary schools that are relevant in the context of Challenges and Solutions in CLIL Implementation: Teachers' Perspectives from Elementary Education.